1965
DOI: 10.1021/ic50030a013
|View full text |Cite
|
Sign up to set email alerts
|

The Preparation and Structure of Cadmium Rhenium Oxide, Cd2Re2O7

Abstract: A cadmium rhenium oxide has been prepared with the formula Cd2Re20~. Its structure is of the pyrochlore type. For the face-centered cubic unit cell, a = 10.219 A. The room temperature resistivity is about 2 X 10~3 ohm cm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
1
2

Year Published

1970
1970
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 0 publications
4
44
1
2
Order By: Relevance
“…Sakai et al also reported superconductivity in the same compound independently [6], and Jin et al reported similar results later [7]. The compound has been known to possess the ideal pyrochlore structure at room temperature, and show metallic conductivity down to T = 4 K [8]. In addition to the observation of superconductivity in Cd 2 Re 2 O 7 we found remarkable anomalies at 200 K both in the electrical resistivity and magnetic susceptibility measurements [5].…”
Section: Introductionsupporting
confidence: 72%
See 1 more Smart Citation
“…Sakai et al also reported superconductivity in the same compound independently [6], and Jin et al reported similar results later [7]. The compound has been known to possess the ideal pyrochlore structure at room temperature, and show metallic conductivity down to T = 4 K [8]. In addition to the observation of superconductivity in Cd 2 Re 2 O 7 we found remarkable anomalies at 200 K both in the electrical resistivity and magnetic susceptibility measurements [5].…”
Section: Introductionsupporting
confidence: 72%
“…Purple octahedral crystals of a few mm in length were obtained. From the facts that both CdO (Cd) and ReO 3 (Re 2 O 7 ) are volatile and that crystals adhered to the walls, it is considered that the crystal growth occurred by a vapor transport mechanism, as discussed in a previous study [8]. The Cd/Re molar ratio was 1.00 ± 0.02 as determined by electron-probe microanalyses (EPMA) and was 0.995 as determined by inductively coupled plasma (ICP) spectrometry.…”
Section: Methodsmentioning
confidence: 99%
“…An alternative recipe was also employed with starting materials CdO (99.9%), Re (99.99%), and ReO 3 (>99%). 9 The final products showed no obvious difference from the first approach. As shown in Fig.…”
Section: Crystal Growthmentioning
confidence: 89%
“…The refined lattice constant was a = 10.2244(6) Å , in fairly good agreement with the previously reported 10.219 Å . 9 The data sets were collected using systematic absences consistent with an F-centered cell (hkl: h + k, h + l, k + l = 2n + l), as the room-temperature structure was known to be pyrochlore. 10 The initial locations of the metal ions were determined by the Patterson heavy-atom method, and the remaining atom positions were revealed by Fourier mapping using the SHELXL97 program.…”
Section: Crystal Structure Inclusions and Stoichiometrymentioning
confidence: 99%
“…The compound exhibits two more phase transitions at T s1 =200 K and T s2 =120 K, where electrical and magnetic properties change dramatically [7,8,9]. The former is of the second order, while the latter is of the first order.…”
mentioning
confidence: 99%